2011
DOI: 10.1074/jbc.m110.173237
|View full text |Cite
|
Sign up to set email alerts
|

Unique Interaction Pattern for a Functionally Biased Ghrelin Receptor Agonist

Abstract: ]substance P, a series of novel, small, peptidemimetic agonists for the ghrelin receptor were generated. By using various simple, ring-constrained spacers connecting the D-Trp-Phe-D-Trp motif with the important C-terminal carboxyamide group, 40 nM agonism potency was obtained and also in one case (wFw-Isn-NH 2 , where Isn is isonipecotic acid) ϳ80% efficacy. However, in contrast to all previously reported ghrelin receptor agonists, the piperidine-constrained wFw-Isn-NH 2 was found to be a functionally biased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…VOLUME 290 • NUMBER 45 • NOVEMBER 6, 2015 sions were drawn from indirect measurement of SRE (25,52) and Rho kinase activation or by the use of a dominant negative mutant of G ␣13 (51). Our data confirm more directly that ghrelin stimulates GHS-R1a-mediated G 13 activation.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 71%
See 1 more Smart Citation
“…VOLUME 290 • NUMBER 45 • NOVEMBER 6, 2015 sions were drawn from indirect measurement of SRE (25,52) and Rho kinase activation or by the use of a dominant negative mutant of G ␣13 (51). Our data confirm more directly that ghrelin stimulates GHS-R1a-mediated G 13 activation.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 71%
“…We took advantage here of G protein activation BRET biosensors (31,32) that directly report on the conformational change of G protein upon activation, to assess whether the partial agonist behavior of these ligands toward IP1 production resulted from their G q partial agonism. Although it was reported that GHSR1a activated G protein-dependent signaling pathways through G q , G i , G o (23,30,50), and G 13 (51), these conclusions were drawn from studies that indirectly measured G protein activation. We monitored here the selective coupling of GHS-R1a to the G protein family using activation biosensors for a panel of G protein subtypes and isoforms (G q , G i1 , G i2 , G i3 , G oa , G ob , G s , G 12 , and G 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few ligands have already been described for the ghrelin receptor, exhibiting some signaling bias, none has been associated with ␤-arrestin. The ghrelin peptide mimetic agonist wfw-Isn-NH 2 supports receptor internalization, G q/11 signaling, and ERK1/2 phosphorylation but not SRE-mediated transcriptional activity or food intake (27). GSK161443, a small molecule ghrelin antagonist of calcium mobilization and inositol phosphate turnover (58), acts in vivo as an antagonist of GH release, an inducer of food intake, and a promoter of increased body weight (59,60), but the mechanistic and physiological basis for this has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…G q/11 and G i/o both mediate Ca 2ϩ release, and G q/11 signaling leads to ERK activation (45), but it is unclear whether G i/o coupling to GHSR1a has the same effect. G q/11 and G 12/13 , but not G i/o , activate SRE transcription downstream of GHSR1a (27), but the contribution of ␤-arrestin is, again, unknown. To measure this signaling, we employed two bioluminescence-based luciferase reporter assays, an SRE assay for MAPK/ERK1/2 activation and an SRF-RE assay, a modified SRE for RhoA/ROCK activation (46,47).…”
Section: Erk1/2 Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation